Improvement of hand hygiene quality and compliance using bioburden measurement and online feedback in Germany - Günther, Frank; Rudolph, Kai; Frank, Uwe; Mutters, Nico T. (Infection control and hospital epidemiology, 2017)
To improve compliance with hand hygiene, a novel method with inclusion of an online reporting system was developed, comprising measurement of total hand bioburden, anonymous online feedback, and onsite training. The intervention significantly improved both compliance and quality of hand hygiene and reduced Staphylococcus aureus incidence. Infect Control Hosp Epidemiol 2016;1-4